Performance of Islamic Religious Education Supervisors in Central Aceh District - Rasidah Rasidah; Tien Rafida; Yusuf Hadijaya (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to analyze the performance of supervisors in improving the quality of Islamic Religious Education (IRE) in Aceh Tengah District by examining their roles in academic and managerial supervision, the strategies employed to strengthen teacher performance, and the internal and external factors that influence their success. Methodology: This study used a descriptive qualitative method with a field study approach; data were collected from IRE supervisors, school principals, and teachers through in-depth interviews, direct observation, and document analysis, followed by thematic analysis. Main Findings: The findings reveal that supervisors play a pivotal role in enhancing learning quality through structured teacher mentoring, support for curriculum development, classroom observation, and performance evaluation. Effective supervisory practices include coaching clinics, collaborative lesson planning, and reflective supervision. However, several challenges hinder optimal implementation, such as limited professional development opportunities, insufficient operational support, constrained supervision coverage areas, and disparities in teachers’ digital competence. Despite these limitations, collaborative strategies involving supervisors, principals, and teachers demonstrate strong potential to resolve supervisory barriers and promote a culture of continuous improvement. Novelty/Originality of this study: The novelty of this study lies in its formulation of an integrated supervisory performance framework that connects the academic, managerial, and digital supervision dimensions within the context of Islamic education, an area underexplored in previous research. The study recommends strengthening competency-based supervisor training, increasing resource allocation, and enhancing inter-agency coordination to ensure sustainable, systemic improvements in the Islamic Religious Education supervisory ecosystem.